1952
DOI: 10.1085/jgp.36.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Independent Functions of Viral Protein and Nucleic Acid in Growth of Bacteriophage

Abstract: 1. Osmotic shock disrupts particles of phage T2 into material containing nearly all the phage sulfur in a form precipitable by antiphage serum, and capable of specific adsorption to bacteria. It releases into solution nearly all the phage DNA in a form not precipitable by antiserum and not adsorbable to bacteria. The sulfur-containing protein of the phage particle evidently makes up a membrane that protects the phage DNA from DNase, comprises the sole or principal antigenic material, and is responsible for att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
271
0
15

Year Published

1971
1971
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,292 publications
(292 citation statements)
references
References 6 publications
1
271
0
15
Order By: Relevance
“…coli B was grown in glycerol-lactate medium [9] to a density of 5 X lo8 cells/ml and infected with North-Holland Publishing Company -Amsterdam T2 phage at a multiplicity of 5.0. Growth was arrested at desired times, by adding chloramphenicol (at a final concentration of 30 /.&ml) and chilling the culture.…”
Section: Methodsmentioning
confidence: 99%
“…coli B was grown in glycerol-lactate medium [9] to a density of 5 X lo8 cells/ml and infected with North-Holland Publishing Company -Amsterdam T2 phage at a multiplicity of 5.0. Growth was arrested at desired times, by adding chloramphenicol (at a final concentration of 30 /.&ml) and chilling the culture.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the change in the meaning of epigenetics that was proposed by Nanney emerged at a time when it was already known that DNA was the molecule that carries the genetic information of organisms (1952) (Avery et al 1944;Hershey & Chase 1952) and when the structural details of nucleic acids were available (1953) (Watson & Crick 1953;Franklin & Gosling 1953a, 1953b. Several important discoveries in epigenetics were yet to be achieved, including Xchromosome inactivation in mammals (1961) (Lyon 1962), cytoplasmic inheritance in Paramecium (1965) (Beisson & Sonneborn 1965), characterization of the structure of nucleosomes (1974) (Kornberg & Thomas 1974) and the discovery of prions (self-replicating proteins capable of transmitting information, in analogy to nucleic acids) (1982) Prusiner et al 1982;Halfmann & Lindquist 2010).…”
Section: From Waddington's Concept and Nanney's Epigenetics To The Prmentioning
confidence: 99%
“…It was also shown that the nucleic acid component of viruses was the infectious component (Hershey and Chase 1952). Consequently, the association of virus-nucleic acid-gene was easy to make.…”
Section: Viruses In Origin-of-life Thinkingmentioning
confidence: 99%